THE EFFECT SCRAPBOOK MEDIA IN IMPROVING THE CREATIVITY OF PRIMARY SCHOOL STUDENTS IN BENGKULU - Abdul Muktadir; Prayuningtyas Angger Wardhani (Journal of Aesthetics, Design, and Art Management, 2022)
Purpose : This study aims to determine the differences in student creativity by using scrapbook media. Research methods : The population in this study were elementary school students in the Air Periukan sub-district. The sample in this study amounted to 100 elementary school fifth-grade students. Data analysis using SPSS 25. Findings: the results showed that there were differences in results with sig <0.05. The average pretest result is 69.18 and the posttest result is 88.02. These results show that students' creativity is higher when using scrapbook media. Thus the scrapbook media influences increasing the creativity of elementary school students. Implications: Scrapbook media is an alternative in increasing the creativity of elementary school students.